2014
DOI: 10.1016/j.apsusc.2014.04.072
|View full text |Cite
|
Sign up to set email alerts
|

Influence of thickness and coatings morphology in the antimicrobial performance of zinc oxide coatings

Abstract: This article appeared in a journal published by Elsevier. The attached copy is furnished to the author for internal non-commercial research and education use, including for instruction at the authors institution and sharing with colleagues. Other uses, including reproduction and distribution, or selling or licensing copies, or posting to personal, institutional or third party websites are prohibited. In most cases authors are permitted to post their version of the article (e.g. in Word or Tex form) to their pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(69 citation statements)
references
References 66 publications
5
55
0
2
Order By: Relevance
“…The studies where ZnO-NPs have demonstrated its anti-pathogenic behavior are plentiful163863737475767778. Its activity has been tested against a plethora of disease causing pathogens, like Salmonella enteritidis , C. albicans , Listeria monocytogenes , and Pseudomonas aeruginosa .…”
Section: Resultsmentioning
confidence: 99%
“…The studies where ZnO-NPs have demonstrated its anti-pathogenic behavior are plentiful163863737475767778. Its activity has been tested against a plethora of disease causing pathogens, like Salmonella enteritidis , C. albicans , Listeria monocytogenes , and Pseudomonas aeruginosa .…”
Section: Resultsmentioning
confidence: 99%
“…Besides, the secondary products such as reactive oxygen species produced by Zn 2+ and Ag + were also harmful to bacteria. Carvalho et al [106] and Jin et al [28] have also proven the enhanced antibacterial activities of simultaneous incorporation of Zn and Ag into Ti. Jin et al [28] believed that the interactions between Zn ions and bacteria were long-range based on the release of Zn ions [27], while the interactions between embedded Ag NPs and bacteria were short-range via the micro-galvanic effects without the release of Ag ions [37,107].…”
Section: Introduction Of Both Metal Nanoparticles and Metallic Compoumentioning
confidence: 99%
“…TiO 2 surfaces have been described as antimicrobial due to its photocatalytic activity after irradiation [13]. However, the antimicrobial activity of TiO 2 thin films without irradiation or without doping the surface with of a known antimicrobial agent such as silver is low against C. albicans [24].…”
Section: Adhesion Of Microorganisms: C Albicansmentioning
confidence: 99%
“…Au, Ag) and oxides (e.g. TiO 2 ) have been also extensively studied due to their functional properties for antibacterial applications [13] and in the study of biological processes in live cells [14]. Moreover, the knowledge acquired about plasmonic materials allowed building chemical and biological sensors [15], which are based on the detection of changes of their optical response due to presence of molecules and biolayers.…”
Section: Introductionmentioning
confidence: 99%